Reading level as a component of the universal culture of the male judo society - Pujszo, Małgorzata; Stępniak, Robert; Adam, Marek (Journal of Education, Health and Sport, 2017)
Objective: To compare the level of reading of people in the judo population as a component of universal culture, against the mean value of reading in the control group and to find possible dependence on reading with judo training. Material and Methods: Tested a group of men training professional and recreationally judo - 36 persons and 36 men in control group using a standard reading questionnaire (behind the National Library) developed for training and education. Results: It showed the qualitative and quantitative differences in reading culture were demonstrated by judo fighters and judo trainers compared the national standard Conclusions: Long-term judo training does not prevent the application of reading culture in everyday life.